Viabilidade de sementes de Piptadenia moniliformis Benth. Pelo teste de tetrazólio - de Azerêdo, Gilvaneide Alves; de Paula, Rinaldo Cesar [UNESP]; Valeri, Sérgio Valiengo [UNESP] (My University, 2011)
Piptadenia moniliformis Benth. is a tree species which is important for beekeeping, as well as being recommended for soil restoration, reforestation, wood production for small civil construction projects, and cattle and sheep forage. Information on how to evaluate seed physiological quality is still scarce and in this was the study aimed to adapt the procedures of the tetrazolium test to assess the viability of P. moniliformis seeds. Four seed lots were scarified in sulphuric acid for 30 min, and soaked between paper towels at 25 °C for 24 hours. The seed coat was then removed and the naked seeds immersed in tetrazolium solutions with concentrations of 0.05, 0.075 and 0.1% for 2, 3, and 4 hours at 35 oC in the dark. Each treatment consisted of four replications of 25 seeds. The embryos were classified according to viability based on the staining patterns. The previous soaking of the seeds for 24 hours at 25 oC between paper towels, followed by the removal of the seed coat and staining of the naked seeds for 4 hours in a 0.075% tetrazolium solution at 35 oC was the most efficient method for evaluating the viability of P. moniliformis Benth seeds.
Determining the viability of Piptadenia moniliformis Benth seeds with the tetrazolium test
Keywords: Forest species; Germination; Rapid tests; Bos; Moniliformis; Ovis aries; Piptadenia moniliformis